Peripherally inserted central catheter: systematic review - Martins, Cassiane (2016)
Introduction: Peripherally Inserted Central Venous Catheter (PICC) is among the expanding technologicaland therapeutic advances in health. It presents the possibility of establishing intravenous therapyof prolonged duration, reducing the number of punctures and insertion at bedside by qualified nurses.Objective: To describe the predominant profile of patients using PICC, the main diagnoses and medicalspecialties that make use of the catheter, associated procedures, average duration of stay, and insertionsites. Method: Systematic review in the electronic databases of the Latin American and Caribbean HealthSciences Literature, Scientific Electronic Library Online, Database of Nursing, and through GoogleScholar search engine. Results and Conclusions: We identified a prevalence of premature, underweightmales less than 7 days old on the date of insertion of PICC. The main indications for the device wereadministering total parenteral nutrition, antibiotics, and medication. The complications were disruption,obstruction, infection, prematurity, and respiratory conditions. The average duration of stay with the catheterwas 11.3 days. Out of 19 studies, 16 were in neonatology. The most accessed veins were the basilicaand cephalic.